Revolutionizing tracheal reconstruction: innovations in vascularized composite allograft transplantation - Zhang, Yiyuan; Wei, Shixiong; Li, Mingqian; Lv, Guoyue (Frontiers in Bioengineering and Biotechnology, 2024)
Tracheal defects, particularly those extending over long segments, present substantial challenges in reconstructive surgery due to complications in vascularization and integration with host tissues.Traditional methods, such as extended tracheostomies and alloplastic stents, often result in significant morbidity due to mucus plugging and mechanical erosion. Recent advances in vascularized composite allograft (VCA) transplantation have opened new avenues for effective tracheal reconstruction. This article reviews the evolution of tracheal reconstruction techniques, focusing on the shift from non-vascularized approaches to innovative revascularization methods that enhance graft integration and functionality. Key advancements include indirect revascularization techniques and the integration of regenerative medicine, which have shown promise in overcoming historical barriers to successful tracheal transplantation. Clinical case studies are presented to illustrate the complexities and outcomes of recent tracheal transplantation procedures, highlighting the potential for long-term success through the integration of advanced vascular engineering and immune modulation strategies. Furthermore, the role of chimerism in reducing graft rejection and the implications for future tracheal transplantation and tissue engineering efforts are discussed. This review underscores the transformative potential of VCA in tracheal reconstruction, paving the way for more reliable and effective treatments for extensive tracheal defects.